2014
DOI: 10.1371/journal.pone.0111563
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiogram-Gated 320-Slice Multidetector Computed Tomography for the Measurement of Pulmonary Arterial Distensibility in Chronic Thromboembolic Pulmonary Hypertension

Abstract: BackgroundWe aimed to study whether pulmonary arterial distensibility (PAD) correlates with hemodynamic parameters in chronic thromboembolic pulmonary hypertension (CTEPH) using electrocardiogram (ECG)-gated 320-slice multidetector computed tomography (MDCT).Methods and FindingsECG-gated 320-slice MDCT and right heart catheterization (RHC) was performed in 53 subjects (60.6±11.4 years old; 37 females) with CTEPH. We retrospectively measured the minimum and maximum values of the cross sectional area (CSA) of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…Our study found that the AD and AC of PA decreased in the following order: MPA, RPA, and LPA, which was consistent with the previous studies. [ 26 ] We also found that the elasticity relativity existed between AA and DA, AA and MPA, LPA and MPA, LPA and RPA, which were positively correlated. No similar research had been reported before.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Our study found that the AD and AC of PA decreased in the following order: MPA, RPA, and LPA, which was consistent with the previous studies. [ 26 ] We also found that the elasticity relativity existed between AA and DA, AA and MPA, LPA and MPA, LPA and RPA, which were positively correlated. No similar research had been reported before.…”
Section: Discussionmentioning
confidence: 59%
“…This is consistent with previous research reports, including echocardiography, MRI, and CT. [ 4 , 5 , 9 , 24 , 25 ] However, the factors of pulse pressure were not taken into account in previous studies on PA elasticity. [ 25 , 26 ] In our research, pulmonary arterial elasticity was defined by the change in cross-sectional area between diastole and systole and then divided by pulse pressure difference. Our method was more comprehensive, and more consistent with the definition of arterial elasticity.…”
Section: Discussionmentioning
confidence: 99%
“…16 PV distensibility is a mechanical property of the pulmonary vessels defined as the relative change in pulmonary arterial diameter or area for a given change in pressure, while PV capacitance is the change in volume associated with a change in pressure (calculated as the ratio of stroke volume to pulmonary pulse pressure, SV/PP), and impedance is the ratio of the pulmonary arterial pressure waveform to the flow over the entire cardiac cycle. 16, 17 PV distensibility has been estimated with different imaging modalities including magnetic resonance imaging, 1820 echocardiography, 21 gated CT, 22, 23 and intravascular ultrasound. 24 However, these techniques are limited in that they all estimate distensibility based on fractional change in diameter or area of the main PA or large PA segments, and do not account for the distensibility of the entire PV circuit including the medium-sized pulmonary arterioles where much of the abnormal vascular remodeling occurs in PH.…”
mentioning
confidence: 99%
“…In present study, out of 40 dogs, male dogs were 25 and female dogs were 15. Kasai et al, [9] found that the right pulmonary artery distensibility (RPAD) index has been used in dogs with pulmonary hypertension (PH) caused by heartworm infection, myxomatous mitral valve disease, or patent ductus arteriosus. The RPAD index and the ratios of acceleration time to peak pulmonary artery flow (AT) and to the ejection time of pulmonary artery flow (ET) were recorded for each dog.…”
Section: Discussionmentioning
confidence: 99%